Analysis of the atmospheric water budget for elucidating the spatial scale of precipitation changes under climate change - Dagan, G; Stier, P; Watson-Parris, D (American Geophysical Union, 2019)
Global mean precipitation changes due to climate change were previously shown to be relatively small and well constrained by the energy budget. However, local precipitation changes can be much more significant. In this paper we propose that for large enough scales, for which the water budget is closed (precipitation [P] roughly equals evaporation [E]), changes in P approach the small global mean value. However, for smaller scales, for which P and E are not necessarily equal and convergence of water vapor still plays a role, changes in P could be much larger due to dynamical contributions. Using 40 years of two reanalysis data sets, 39 CMIP5 models and additional numerical simulations, we identify the scale of transition in the importance of the different terms in the water budget to precipitation to be ~3500-4000 km and demonstrate its relation to the spatial scale of precipitation changes under climate change.